Birds of a feather: informal recruitment practices and gendered outcomes for screenwriting work in the UK film industry - Wreyford, Natalie (The Sociological review (Keele), 2015)
The film industry offers an exemplary case study for examining the recruitment processes to which the ‘socialized worker’ (Gill and Pratt, 2008) is subject. Even among the creative industries, film is exceptional in its reliance on networking and word of mouth as its primary – and in many cases only – tool for recruitment and for identifying the ‘right’ candidate for the job (Blair, 2000a). Increasingly there is evidence that reliance on personal networks and informal employment practices has different outcomes for men and women (Grugulis and Stoyanova, 2012). Hiring on short-term contracts in a context of ambiguity, risk and uncertainty, necessitates reliance on social networks and informal subjective criteria, with outcomes that reinforce the status quo (Bielby and Bielby, 1999). Fenstermaker, West and Zimmerman argue that to overcome gender inequality ‘we will need to understand the mechanisms by which it is sustained in institutional social arrangements’ (Fenstermaker et al., 2002: 38). This article will unpack how recruitment procedures that rely on ‘connections’ and ‘affinities of habitus’ (Bourdieu, 1984: 151) can contribute to the way that gender inequality is sustained for screenwriters.